Preface - P.G.R. de Villiers; D.F. Tolmie (Acta Theologica)
On the occasion of his 80th birthday, this volume celebrates Kees Waaijman for his distinguished career and scholarship in Spirituality over a period of 60 years. Researchers in the field of mysticism and spirituality from all over the globe offer contributions in honour of one of the bestknown scholars in the field, in recognition of his singular contribution to research on spirituality.